Poly[μ-chlorido-[μ(4)-5-(4-pyridyl)tetrazolato]dicopper(I)] - Wang, Cun-Kuan (International Union of Crystallography, 2009)
The title three-dimensional coordination polymer, [Cu(2)Cl(C(6)H(4)N(5))](n), is the product of the hydrothermal reaction of CuCl(2)·2H(2)O and 5-(4-pyridyl)-1H-tetrazole (4-Hptz). The two independent Cu(I) ions are coordinated in distorted tetrahedral and distorted trigonal coordination environments. In the unique 5-(4-pyridyl)-1H-tetrazolate ligand, the dihedral angle between the pyridine and tetrazole rings is 17.3 (2)°.